2018
DOI: 10.3168/jds.2018-15096
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid bacteria with cholesterol-lowering properties for dairy applications: In vitro and in situ activity

Abstract: Cholesterol-lowering activity is one of the most promising properties of lactic acid bacteria with probiotic characteristics. In the present study, 58 potentially probiotic lactic acid bacteria were tested for their ability to survive in vitro digestion and reduce cholesterol in a medium containing cholesterol and bile acids. The best-performing strains (Lactobacillus casei VC199, Lactobacillus paracasei ssp. paracasei SE160 and VC213, Lactobacillus plantarum VS166 and VS513, Enterococcus faecium VC223, and En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 64 publications
1
52
1
Order By: Relevance
“…Cholesterol lowering capability is one of the essential characteristics of lactic acid bacteria with probiotic potential. 41,70 It prompted us to investigate the efficiency of CFM of A29 on fat depositions in 3T3-L1 adipocytes. Furthermore, Bodyweight, adipose tissue mass reduction, and clinical parameter alterations in the blood by live A29 supplement to HFD-fed mice were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol lowering capability is one of the essential characteristics of lactic acid bacteria with probiotic potential. 41,70 It prompted us to investigate the efficiency of CFM of A29 on fat depositions in 3T3-L1 adipocytes. Furthermore, Bodyweight, adipose tissue mass reduction, and clinical parameter alterations in the blood by live A29 supplement to HFD-fed mice were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al (2011) isolated 12 Lactobacillus strains from kimchi and showed the ability to reduce cholesterol level by more than 40% in the in vitro test. Albano et al (2018) reported that Lactobacillus casei VC199, Lactobacillus paracasei ssp. paracasei SE160 and VC213, Lact.…”
Section: Introductionmentioning
confidence: 99%
“…Though studies have reported the BSH activity, hypo-cholesterolemic effect, and probiotic properties of Enterococcus strains isolated from animal and human gut (Hlivak et al, 2005; Hyrslova et al, 2016; Zhang et al, 2017) and fermented food products (Guo et al, 2016; Albano et al, 2018; Nami et al, 2019), the BSH activity and cholesterol-lowering ability of Enterococcus isolated from environmental niches, like aquatic and terrestrial plants, soil, and water, have not been reported. Bacteria isolated from environments in which bile salts are absent usually do not demonstrate BSH activity (Elkins et al, 2001; Moser and Savage, 2001; Ahn et al, 2003).…”
Section: Introductionmentioning
confidence: 99%